Sistem Informasi Manajemen Surat Masuk Dan Keluar (SIM-SMK) Responsif Berbasis Web Menggunakan Metode Design Thinking - Hardiansyah Putra (Bulletin of Computer Science Research, 2023)
The web-based Entry and Exit Management Information System (SIM-SMK) has become a critical foundation in dealing with the complexity of mail management in the modern business environment. The research introduced a web-based responsive SIM-SMK, developed using the Waterfall software development methodology. The Waterfall method was chosen because of its ability to provide a structured structure and clear stages in system development. The system is designed to improve efficiency, accuracy, and speed in inbound and outbound mail management. Key features include automatic mail reception, real-time mail status tracking, and easily accessible digital archives. Simulation and testing are carried out at every stage of development to ensure system reliability and compliance with user requirements. This web-based SIM-SMK implementation demonstrates high responsiveness in responding to user requests, enabling access from a variety of devices and platforms. With integration of the latest technology, such as a user-friendly interface, cloud-based management, and encrypted data security, this SIM-SMK meets security and information availability standards.